Banned, Challenged, Questioned, or Lost? Information Access and the Path to an Information‐Resilient Society: ASIS&T Midwest Regional Chapter. Issue 1 (14th October 2022) - Brannon, Brittany; Bossaler, Jenny; Dickey, Timothy J; Hajibayova, Lala; Kohlburn, Joe; Oltmann, Shannon M; Smith, Andrew J. M.
Abstract: Historically, librarians and information professionals have professed and supported tenets of free thought and free access to all information. Guides, literature, conference sessions, and classroom exercises help guide LIS students and librarians through the provision of controversial materials. However, information professionals work within the political and practical boundaries of their institutions. They rely on imperfect and mediated technologies for access to information and communication. The reality is that such constraints, as well as external politics and broader societal and cultural challenges, can and do affect access to information. Librarians are thus limited in their impact by both internal and external factors. This panel joins the perspectives of LIS researchers and practitioners. The discussion will demonstrate disparate threads that exemplify current research on information access challenges, successes, and opportunities in a variety of contexts. Part of contributing to an information‐resilient society is being aware of the many ways that society censors or limits access to ideas and knowledge. The panel will discuss ways to create more equitable access to technology and digital information, provision of health and wellness information, the impact of user‐generated social media reading recommendations, persistent access to dissertation research information, and the hotly contested space of drag story‐times at libraries. The research projects illustrate a wellspring of opportunities for resistance against societal limitations on knowledge and illustrate ways to reinforce core values of the profession.